Validación de un registro observacional para la detección del Síndrome del Emperador en el aula. - Rabadán-Rubio, José Antonio; Giménez-Gualdo, Ana María (Asociación de Análisis del Comportamiento, 2014)
Educating children becomes dif􀃀cult because of social changes. However it is more dif􀃀cult with those who consider themselves as supreme heroes at home and ill-treat to their parents. These children and teenagers are considered part of “Emperor’s syndrome” which has worryingly increasing, justifying the need to promote an early detection of these behaviour disorders at schools. At this point, the aim is to present an observational scale directed to primary and secondary teachers and its validation process through inter-judges. The results shows a high reliability index of the tool as useful to detect this syndrome in classrooms in order to refer students to specialists.
Política de acceso abierto tomada de: https://www.ijpsy.com/normas.html
Keywords: Niños - Trastornos de la conducta; Emperor's syndrome; Adolescence; Validation; Observational tool